Application of Transcutaneous Electrical Nerve Stimulation in Dentistry - Mutum Sangeeta Devi; Manju J; Ravi Ranjan; Takhellambam Dhanapati Devi; Binita Sorokhaibam (Institute of Medico-legal Publications Pvt Ltd, 2021)
Transcutaneous electrical nerve stimulation (TENS) is a non-pharmacological procedure commonly used by medical and paramedical practitioners in a variety of circumstances for the treatment of acute and chronic pain. Similarly, it can be used during different dental procedures to relieve pain as well as pain due to different conditions that affect the maxillofacial area